The effect of seasonality on fish species composition and abundance in Rungan river floodplain, Palangkaraya, Central Kalimantan - BAMBANG SULISTIYARTO; DEDI SOEDHARMA; MOHAMMAD FADJAR RAHARDJO; SUMARDJO SUMARDJO (Society for Indonesian Biodiversity, 2007)
Tropical floodplain rivers are home to the largest fraction of freshwater fish diversity and as such should be a focal point of fish conservation efforts. The aim of this study was to inventory of the fish fauna and analyzing the effect of seasonality on fish species composition and abundance in the Rungan river floodplain at Palangkaraya Municipality. The results of this study provide background data for conserving fish resources. Fishes were sampled at monthly intervals between May 2005 and April 2006 with gillnets of standardized dimensions with several mesh sizes. These were carried out at three stations with different habitat type, includes forested swamp, opened swamp, and river. A total of 4278 fishes were collected consisting of 50 species and 19 families. Seasonality effects on fish species composition andabundance in forested swamp and river. Fish species composition and abundance in opened swamp tend not to drive by seasonality.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: species composition, fish, floodplain, Kalimantan, seasonality.